New media-new voices: satirical representations of Nigeria's socio-politics in Ogas at the top - Ephraim, Philip Effiom; Akter, Tutku; Gansinger, Martin (Routledge Journals, Taylor & Francis Ltd, 2017)
New media are increasingly providing spaces and opportunities for media houses and activist groups engaged in socio-political reform in Africa. In Nigeria, social media are becoming platforms for communicating messages of resistance against oppressive political and exploitative economic power structures. This study analyzed Ogas at the top (OATT), an online puppetry series by Buni TV, as a way of examining new platforms and message content in Nigeria's rapidly changing media sphere. Relying on semiotics and critical discourse analysis perspectives, the study analyzed select episodes of the series, to gauge how producers constructed powerful visual and linguistic messages to boldly satirize social injustices perpetrated by Nigeria's political elites.
Keywords: Social media; puppetry; Ogas at the top; Nigeria's socio-politics; power abuse